Contact and Social Distance to Drug Trafficking of Rural and Urban Adolescents - González Navarro, José Roberto (Consorcio de Universidades Mexicanas A.C., 2022)
The drug trafficking acceptance is an important problem in Mexico. It is seen, by broad sectors, as an opportunity for social mobility despite its consequences. The aim of this investigation was to compare the exposure and acceptance degree of the phenomenon in adolescents in their socialization spaces. The present cross-sectional, correlational research compared contact and social distance to drug trafficking in two groups of adolescents (urban and rural) in Nayarit, using the Psychosocial Proximity to Drug Trafficking Scale. The results showed less social distance with drug traffickers in rural adolescents; different patterns in contact with narcoculture productions and positive correlation between level of contact, social distance and contact with information or cultural productions of drug trafficking. This suggests that, besides current contact with drug traffickers, information and contact with productions related to drug trafficking could influence the intention to contact their agents.